Community pharmacists and chronic pain: A qualitative study of experience, perception, and challenges. Issue 3 (1st September 2020) - Tabeefar, Hamed; Chang, Feng; Cooke, Martin; Patel, Tejal
ABSTRACT: Background : Patients suffering from chronic pain frequently ask pharmacists for advice. Aims : This study was prompted by inadequacies in the available body of literature reporting on pharmacists' experiences with providing care for patients with chronic pain in the community setting. Methods : A qualitative investigation of Ontario community pharmacists' experiences was carried out. Participants were interviewed using a semistructured guide. Interviews were analyzed using thematic analysis, influenced by grounded theory. Results : This study revealed that pharmacists were knowledgeable and empathetic toward patient concerns. Challenges in their role included financial factors, patient access to multimodal treatment options, potential for harm associated with opioid use, inadequate monitoring, and gaps in training. Conclusions : This study reports community and Family Health Team pharmacists' experiences caring for patients with chronic pain and perceptions of their professional role, including strengths and limitations, and identifies perceived challenges in the health care system.